Let $S = k[x_{i,j}\mid 1\leq i\leq n, 1\leq j\leq m]$ be a polynomial ring over an arbitrary field $k$. Let $M$ be a generic $n\times m$ matrix of indeterminates in the ring $S$ where $n\leq m$. For any $k\leq n$, let $M'$ denote the matrix $M$ with column $k$ removed and let $M_k$ denote the matrix $M$ restricted to columns $1, \ldots, k$. Consider the ideals $J_1 = I_n(M')$, the ideal of maximal minors of $M'$, and $J_2 = I_k(M_k)$, the ideal of maximal minors of $M_k$. I need to show that

$$ J_1\cap J_2 = J_1\cdot J_2 $$

or, equivalently,

$$ Tor_1(S/J_1,S/J_2) = 0. $$

I feel like this must follow somehow from the fact that NO determinants in $J_1$ contain variables from column $k$, but EVERY determinant in $J_2$ contains variables from column $k$, but I am not sure how to show it.


1 Answer 1


After some thought, I came up with the following answer to my own question.

First, observe that $$ \mathbf{x} = (x_{1,k}, \ldots, x_{n,k}) $$ is a regular sequence over $R/I_n(M')$. Take an element $f\in I_n(M')\cap I_k(M_k)$. Then $$ f = \sum_{I\in I_n(M')} c_I [i_1, \ldots, i_n] = \sum_{J\in I_k(M_k)} d_J [j_1, \ldots, j_k]. $$ Expanding the minor $[j_1,\ldots, j_k]$ along column $k$ using the Laplace expansion, one obtains the equality \begin{align*} \sum_{I\in I_n(M')} c_I [i_1, \ldots, i_n] &= \sum_{J\in I_k(M_k)} d_J \left(\sum_{\ell\in \{1,\ldots, n\}} (-1)^\ell \, x_{\ell, k} \, [1, \ldots, \hat \ell, \ldots, n\mid j_1, \ldots, j_{k-1}]\right)\\ &= \sum_{J\in I_k(M_k)} \sum_{\ell\in \{1,\ldots, n\}} (-1)^\ell d_J\cdot x_{\ell,k}\, [1, \ldots, \hat \ell, \ldots, n\mid j_1, \ldots, j_{k-1}]. \end{align*} Observe that since $\mathbf{x}$ is regular over $R/I_n(M')$, each $d_J\cdot [1, \ldots, \hat \ell, \ldots, n\mid j_1, \ldots, j_{k-1}]$ must be in $I_n(M')$. But $I_n(M')$ is a prime ideal, so either $d_J$ or $[1, \ldots, \hat \ell, \ldots, n\mid j_1, \ldots, j_{k-1}]$ must be in $M'$. Clearly $[1, \ldots, \hat \ell, \ldots, n\mid j_1, \ldots, j_{k-1}]$ is not in $M'$, so we have that $d_J$ must be in $I_n(M')$, so $I_n(M')\cap I_k(M_k) = I_n(M')\cdot I_k(M_k)$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.